Corneal stromal cells selectively inhibit production of anti-inflammatory cytokines by activated T cells - Holán, V; Vítová, A; Pindjáková, J; Krulová, M; Zajícová, A; Filipec, M (Clinical and experimental immunology, 2004)
The eye has been described as an immunologically privileged site where immunity is purely expressed. It has been demonstrated that administration of antigen into the eye induces only a weak immune response. However, the anterior part of the eye represents an important protective barrier against pathogens and other harmful invaders from the outer environment. Therefore, effective immune mechanisms, which operate locally, need to be present there. Because the cornea has been shown to be a potent producer of various cytokines and other molecules with immunomodulatory properties, we investigated a possible regulatory role for the individual corneal cell types on cytokine production by activated T cells. Mouse spleen cells were stimulated with the T cell mitogen concanavalin A in the presence of either corneal explants or cells of corneal epithelial or endothelial cell lines and the production of T helper 1 (Th1) or Th2 cytokines was determined by enzyme-linked immunosorbent assay (ELISA) or reverse transcription-polymerase chain reaction (RT-PCR). We found that the cornea possesses the ability to inhibit, in a dose-dependent manner, production of the inhibitory and anti-inflammatory cytokines interleukin (IL)-4 and IL-10 by activated T cells. The production of cytokines associated with protective immunity [IL-2, IL-1beta, interferon (IFN)-gamma ] was not inhibited under the same conditions. Corneal explants deprived of epithelial and endothelial cells retained the ability to suppress production of anti-inflammatory cytokines. This suppression was mediated by a factor produced by corneal stromal cells and occurred at the level of cytokine gene expression. We suggest that by this mechanism the cornea can potentiate a local expression of protective immune reactions in the anterior segment of the eye.
Keywords: interferon gama; Interleukin-2; Interferon-gamma; Corneal Stroma; T-Lymphocytes; Mice, Inbred BALB C; Interleukin-4; stroma rohovky; interleukin-1; cytokiny; Interleukin-1; T-lymfocyty; Coculture Techniques; mužské pohlaví; interleukin-10; Mice; Cytokines; Concanavalin A; slezina; interleukin-2; interleukin-4; polymerázová řetězová reakce s reverzní transkripcí; aktivace lymfocytů; ženské pohlaví; ELISA; Culture Techniques; zvířata; Lymphocyte Activation; kultivační techniky; myši inbrední BALB C; kokultivační techniky; myši; Reverse Transcriptase Polymerase Chain Reaction; Enzyme-Linked Immunosorbent Assay; Interleukin-10; Female; Spleen; konkanavalin A; Male; Animals